2016 European guideline on donovanosis. (July 2016) - O'Farrell, Nigel; Moi, Harald
Donovanosis is a rare sexually transmitted infection now mainly seen in sporadic cases in Papua New Guinea, South Africa, India, Brazil and Australia. The causative organism is Calymmatobacterium granulomatis, though a proposal has been put forward that the organism be reclassified as Klebsiella granulomatis comb nov . The incubation period is approximately 50 days with genital papules developing into ulcers that increase in size. Four types of lesions are described – ulcerogranulomatous, hypertrophic, necrotic and sclerotic. The diagnosis is usually confirmed by microscopic identification of characteristic Donovan bodies on stained tissue smears. More recently, polymerase chain reaction methods have been developed. The recommended treatment is azithromycin 1 g weekly until complete healing is achieved.